Doctrinal analysis of the actus criminal offenses encroaching on ecological safety in the context of the new Criminal Code of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
In this article the doctrinal analysis of the actus criminal offenses encroaching on ecological safety in the context of the new Criminal Code. The author gives his vision of the objective side of these criminal offenses. Recommendations for further improvement of the criminal law as part of the objective side of the criminal offenses encroaching on ecological safety.Key words: ecological safety, environmental criminal offenses, the objective side of the criminal offenses of the actus, doctrinal analysis.